A peak power reduction based demand response strategy and load factor maximization oriented electric vehicle parking lot energy management strategy - Erdinc, Ozan; Tascikaraoglu, Akin (PAMUKKALE UNIV, 2018)
Together with the increasing attention on the electrification of transportation systems, the studies realized on electric vehicles have gained a great acceleration. However. as the electric vehicles are connected to the electric power system from the distribution level, an important power demand increase will occur in the system due to the electric vehicle charging requirements. Even the coordination of individual electric vehicles so as to bring minimum loading to the distribution system is significantly hard, especially the management of the relevant charging process within the electric vehicle parking lots is an effective option. Specifically, this issue has been linked with the demand response concept in smart grid content In this regard, in this study an energy management strategy that can ensure the requirements of a peak power reduction oriented demand response strategy and can provide an operation that maximizes the load factor of the relevant charging power variation is proposed.
Keywords: Demand response; Electric vehicles; Energy management system; Load factor; Peak power reduction; Engineering